2020
DOI: 10.1111/andr.12838
|View full text |Cite
|
Sign up to set email alerts
|

The metastatic potential of seminomatous germ cell tumours is associated with a specific microRNA pattern

Abstract: Background Seminomatous germ cell tumours (SGCT) are the most frequent malignancy in young men. Reliable prognostic biomarkers for the prediction of metastasis at diagnosis and the risk of relapse in clinical stage I (CSI) are lacking. Adjuvant therapies carry a risk of overtreatment, whereas salvage therapies have a risk of high toxicities. Thus, the identification of reliable prognostic biomarkers is highly desirable to identify patients who will benefit from early adjuvant treatment. MicroRNAs (miRNAs) regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Knowledge of microRNA hsa-miR-758-5p and its role in cancer progression are limited. This miRNA was differentially expressed in metastatic compared with non-metastatic seminomatous germ cell tumors ( 32 ). However, the mechanistic connection between expression of this microRNA and aGCT recurrence is still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of microRNA hsa-miR-758-5p and its role in cancer progression are limited. This miRNA was differentially expressed in metastatic compared with non-metastatic seminomatous germ cell tumors ( 32 ). However, the mechanistic connection between expression of this microRNA and aGCT recurrence is still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies on hsa-miR-371a-5p, and they are mainly focused on tumors and inflammation-related studies. Ernst et al's research showed that the miRNA microarray results changed significantly in term and preterm placentas, among which hsa-miR-371a-5p showed significant changes (32). However, Jang et al used RT-qPCR to verify the samples (both term and preterm placentas) in large quantities and found that hsa-miR-371a-5p did not change significantly, while hsa-miR-371a-5p was confirmed to be able to regulate the inflammatory target gene LEF1 found in the samples (33).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, miR-371a-3p may have limited utility as a tool for risk stratification. There are, however, some other members of miRNA family such as miR-29c-5p, miR-506-3p, miR-1307-5p, and miR-371a-5p that have shown potential capability to act as a prognostic marker in SGCT [ 44 ]. The results of currently recruiting trials, where prospective and serial collection of miRNAs are performed at different stages, will provide more definitive evidence in this regard.…”
Section: Prognostic Markermentioning
confidence: 99%